2017
DOI: 10.3892/or.2017.6026
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a human primary pancreatic cancer mouse model to examine and investigate gemcitabine resistance

Abstract: Pancreatic cancer is one of the most fatal types of cancer and is associated with a dismal prognosis. Gemcitabine-based chemotherapy is clinically used for the treatment of advanced pancreatic cancer. However, many forms of pancreatic cancer have acquired resistance to gemcitabine. In order to prevent patients from suffering from the side effects of chemotherapy and to have the chance to receive more effective intervention, assessment of whether the patient pancreatic cancer cells are resistant to gemcitabine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
6
0
3
Order By: Relevance
“…Patients with t(8;21) demonstrated overall hypomethylation as compared to other groups, with all of the top 50 probes (mapping to 44 unique genes) significantly hypo-methylated as compared to non t(8;21) cases ( Table 2 ). These genes included MCF2L , a guanine nucleotide exchange factor implicated in gemcitabine resistance that also impacts Rho/Rac signaling [ 35 ]; SLC9A1 , involved in maintaining alkaline pH and Warburg effect and associated with chemo-resistance in solid tumors; FAM120B located in close proximity to MLLT4 , a known fusion partner in leukemia; DZIP1 , zinc finger protein 1, an oncogene involved in wnt/B catenin and Hedgehog signaling; genes with potential tumor suppressive effects; PTPRF that acts via deactivating ERK1/2 signaling; LARP1 that interacts with oncogenic transcripts and regulates mTOR post-transcriptionally with impact on CDK9 and mTOR interaction in leukemia [ 36 ]. A few selected examples from the t(8:21) specific paired methylation and expression signatures, are shown in Figure 3 panels A and B ( Table S3 shows the detailed results).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with t(8;21) demonstrated overall hypomethylation as compared to other groups, with all of the top 50 probes (mapping to 44 unique genes) significantly hypo-methylated as compared to non t(8;21) cases ( Table 2 ). These genes included MCF2L , a guanine nucleotide exchange factor implicated in gemcitabine resistance that also impacts Rho/Rac signaling [ 35 ]; SLC9A1 , involved in maintaining alkaline pH and Warburg effect and associated with chemo-resistance in solid tumors; FAM120B located in close proximity to MLLT4 , a known fusion partner in leukemia; DZIP1 , zinc finger protein 1, an oncogene involved in wnt/B catenin and Hedgehog signaling; genes with potential tumor suppressive effects; PTPRF that acts via deactivating ERK1/2 signaling; LARP1 that interacts with oncogenic transcripts and regulates mTOR post-transcriptionally with impact on CDK9 and mTOR interaction in leukemia [ 36 ]. A few selected examples from the t(8:21) specific paired methylation and expression signatures, are shown in Figure 3 panels A and B ( Table S3 shows the detailed results).…”
Section: Resultsmentioning
confidence: 99%
“…MC2L is one of the guanine nucleotide exchange factors, which may link the potential signalling pathway through RAC1, RHOA and CDC42, also named DBS/DBLs Big Sister, belonging to the DBL family [ 39 ]. Research has shown that MCF2L/DBS MCF2L may play an important role in gemcitabine resistance of primary pancreatic cancer patients [ 40 ], which may provide some explanations for the causes of TNBC chemotherapy resistance. It should be noted that the EPB41 gene encodes Erythrocyte Membrane Protein Band 4.1, which belongs to the family of cytoskeletal proteins that play important roles in maintaining normal cell morphology and cell adhesion, migration, division, and intercellular signalling [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Para além da pesquisa básica e pré-clínica, existe também a perspectiva de aplicação clínica dos PDXs na elaboração de estratégias terapêuticas personalizadas, nas quais atuariam como avatares dos pacientes para o teste e seleção do melhor regime de tratamento (Jin et al, 2010b;Hidalgo et al, 2011;Villarroel et al, 2011;Kamiyama et al, 2013;Malaney et al, 2014;Witkiewicz et al, 2016;Cheng et al, 2017;Dong et al, 2017;Perales-Patón et al, 2017;Williams, 2017). Por outro lado, embora representem um novo e valioso instrumento no arsenal dos pesquisadores na guerra contra o câncer, os PDXs não são modelos perfeitos e também apresentam as suas limitações (Kelland, 2004;Kopetz et al, 2012;Choi et al, 2014;Hidalgo et al, 2014;Byrne et al, 2017;Cheng et al, 2017;Dong et al, 2017;Lin et al, 2017a;Wen et al, 2017;Williams, 2018). Por exemplo, o estabelecimento dos xenotransplantes nem sempre é bem sucedido, havendo taxas de sucesso significativamente baixas para determinados tipos de câncer, o que se configura como um obstáculo importante à sua eventual aplicação em medicina personalizada (Hidalgo et al, 2014;Dong et al, 2017).…”
Section: Modelos Pré-clínicos No Estudo Do Câncer: a Importância Dos unclassified
“…Como exemplo, a gradual substituição do estroma humano pelo estroma murino ao longo das passagens pode afetar o efeito de drogas dirigidas contra esse componente do tumor, como é o caso dos agentes antiangiogênicos (Kelland, 2004;Kopetz et al, 2012;Hidalgo et al, 2014;Cassidy et al, 2015;Byrne et al, 2017;Wen et al, 2017;Williams, 2018). De modo semelhante, o comprometimento do sistema imunológico nos camundongos receptores torna os PDXs incapazes de recapitular com precisão as complexas interações entre as células neoplásicas e as células imunes, restringindo assim a avaliação de terapias com agentes imunomoduladores (Choi et al, 2014;Hidalgo et al, 2014;Cassidy et al, 2015;Byrne et al, 2017;Cheng et al, 2017;Wen et al, 2017;Williams, 2018). Outro inconveniente que pode causar equívocos nas conclusões acerca do efeito de medicamentos é o fato de que PDXs gerados a partir de tumores resistentes à terapia podem eventualmente perder essa característica, e se tornar novamente suscetíveis (Sereti et al, 2018).…”
Section: Modelos Pré-clínicos No Estudo Do Câncer: a Importância Dos unclassified
See 1 more Smart Citation